COVID-19 news a way to promote statistics classes - Silvestre, Cláudia (2022)
There is no doubt that Statistic plays an important role in our information-driven society. And news about coronavirus pandemic has reinforced statistical literacy importance. But teaching statistics could be a challenge due to the fact that some students do not feel comfortable with numbers and have no interest in statistics. How to engage students and motivate them to learn? To overcome this difficulty, we conducted a statistical study on the media coverage COVID-19 pandemic, mainly using news headlines. News were analysed using Python language. Analysing press news helped students to get more motivated and to improve their statistical skills.